The Relationship of Working Mothers and Dependency Level on Pre-School Children Gadgets’ Use - Andi Lis Arming Gandini; Umi Kulsum; Emmy Putri Wahyuni (International Journal Labs, 2023)
Currently, many housewives decide to work, with these conditions it has an impact on limited time to interact directly with children. This causes children to be further away from parental supervision and assistance, especially in using gadgets. This study aimed to determine the relationship between working mothers and the level of dependency on gadget use in preschool-aged children. The research method used is an analytic study with a cross-sectional design. A sample of 303 mothers with preschool-age children in all public kindergartens in Samarinda City. The level of dependency on gadget use in preschool-age children is based on the standard length of time using gadgets in a day according to the Indonesian Pediatrician Association (IDAI). Then the data obtained were analyzed using the Chi-Square test. The results of the analysis obtained-valuable <0,05 (0,001), which means that there is a relationship between working mothers and the level of dependence on gadget use in preschool-aged children. The use of gadgets at preschool age must be supervised and assisted, especially by parents, not only mothers but also families.